MYT1L deficiency impairs excitatory neuron trajectory during cortical development - Allen Yen; Simona Sarafinovska; Xuhua Chen; Dominic D. Skinner; Fatjon Leti; MariaLynn Crosby; Jessica Hoisington-Lopez; Yizhe Wu; Jiayang Chen; Zipeng A. Li; Kevin K. Noguchi; Robi D. Mitra; et al. (Nature Communications)
Abstract Mutations reducing the function of MYT1L, a neuron-specific transcription factor, are associated with a syndromic neurodevelopmental disorder. MYT1L is used as a pro-neural factor in fibroblast-to-neuron transdifferentiation and is hypothesized to influence neuronal specification and maturation, but it is not clear which neuron types are most impacted by MYT1L loss. In this study, we profile 412,132 nuclei from the forebrains of wild-type and MYT1L-deficient mice at three developmental stages: E14 at the peak of neurogenesis, P1 when cortical neurons have been born, and P21 when neurons are maturing, to examine the role of MYT1L levels on neuronal development. MYT1L deficiency disrupts cortical neuron proportions and gene expression, primarily affecting neuronal maturation programs. Effects are mostly cell autonomous and persistent through development. While MYT1L can both activate and repress gene expression, the repressive effects are most sensitive to haploinsufficiency, likely mediating MYT1L syndrome. These findings illuminate MYT1L’s role in orchestrating gene expression during neuronal development, providing insights into the molecular underpinnings of MYT1L syndrome.